Protective effect of Diospyros kaki L. leaves extract against oxidative damage and inflammation in the testicular ischemia-reperfusion model in rats - Yurtal, Ziya; Kulualp, Kadri; Ozkan, Hueseyin; Kutlu, Tuncer; Alakus, Halil; Aslan, Abdullah; Kaya, Ufuk (Natl Inst Science Communication-Niscair, 2023)
The Oriental persimmon, Diospyros kaki L., native of China, with its bioactive compounds from leaves, flavonoids and polyphenols in particular, possess antibacterial, antiallergic, anti-inflammatory, neuroprotective and antihypertensive properties. Though, the anti-inflammatory and antioxidative effects of the D. kaki leaves have beneficial effects in I/R injury in the brain, the same has not been investigated in testicular I/R injury until now. Hence, in the present study, we investigated its leaf extract against oxidative damage and inflammation in the testicular ischemia-reperfusion model. Thirty-two male rats were randomly and equally divided into four groups. While saline (SF) was given to the control and ischemia/reperfusion (I/R) groups for 5 days, Diospyros kaki (DK) and I/R+DK were given 200 mg/kg of DK leaf extract. Afterwards, left orchiectomy was performed in control and DK, and testicular torsion was performed in I/R and I/R+DK for 2 hours. All rats were sacrificed 24 hours after procedures and samples were collected. Compared to the control, I/R had high MDA levels, low GSH and GSH-Px levels; compared to the I/R, MDA levels of the I/R+DK were lower, and the GSH and GSH-Px levels were higher. In I/R, the presence of congestion and hemorrhage were determined and the deterioration in seminiferous tubule structure and spermatogenesis were less in the I/R+DK. TNF-alpha, COX-2, BCL-2, and BAX genes expressions were significantly lower in the I/R+DK group. TNF-alpha and COX-2 proteins were higher in I/R and I/R+DK groups, while NRF2 was higher in I/R+DK. These results show that DK leaves extract has crucial protective effect against oxidative damage and inflammation in the I/R model of rats.
Keywords: Chinese persimmon; Japanese persimmon; Oriental persimmon; Reactive oxygen species (ROS); Testicular; torsion